The sustainable urban mobility plans in the EU and their relevance to car manufacturers - a concept of future mobility - Von Geldern, Felix; Kolář, Petr; Piechottka, Fabian; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2020)
Emerging trends, innovation and new technologies are predicted to change the paradigm of passenger mobility. Simultaneously, governments are promoting the approach of sustainability awareness. On a European level, Sustainable Urban Mobility Plans are being developed to streamline these trends and assure sustainable interaction between social welfare, environmental protection and economic growth. There is a limited number of papers on the potential impact that sustainable mobility planning has on the mentioned area of conflict. The research question of the thesis was the following: “How do the EU's Sustainable Urban Mobility Plans influence the social welfare, environmental and economic growth, in particular in the context of the automotive Original Equipment Manufacturers?”The thesis replied to the question by assessing the sustainability of the European Sustainable Urban Mobility Planning approach that emerged from identified trends. The sustainability assessment was done via expert interviews by taking 11 indicators into account that were attributed to the three pillars of sustainability, namely social welfare, environmental protection and economic growth.The outcome of the thesis, however, has shown that SUMP does not develop urban mobility equally in regard to the three pillars of sustainability. The evaluation of sustainability indicators has demonstrated that SUMP is mainly focusing on the environmental impact. It furthermore shows a good to excellent emphasis on social welfare but fails to sufficiently address economic growth to be truly sustainable in the long run.Car manufacturers are facing an uncertain, yet challenging future. Future success heavily depends on how flexible CEOs can adapt their business model to the currently emerging trends, especially in terms of managing the area of conflict between the opposing technological, societal and environmental trends.
Moreover, it relies on the capability of car manufacturers to commit to the European noise and air pollution regulations and hence the development of alternative powertrains.
Vedoucí práce: Petr Kolář
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses